Peran Guru Pendidikan Pancasila Dalam Menumbuhkan Kepercayaan Diri (Self Confidence) Peserta Didik Di Smpn 1 Sukoharjo - Zahra Nur Farida; Berchah Pitoewas; Rohman .; Devi Sutrisno Putri; Febra Anjar Kusuma (Jurnal Pendidikan Sosial Dan Konseling, 2026)
This study aims to determine the role of Pancasila Education teachers in fostering self-confidence in students at SMP Negeri 1 Sukoharjo. Self-confidence is a crucial aspect influencing students' courage to express opinions, participate in learning, and believe in their abilities. This study employed a descriptive method with a quantitative approach. The study population was 256 eighth-grade students, with a sample of 64 respondents determined using proportionate random sampling. Data collection was conducted through questionnaires and interviews, and data analysis was conducted using SPSS. The results indicate that Pancasila Education teachers play a significant role in fostering student self-confidence, with indicators as educators (95.31%), facilitators (82.81%), and evaluators (87.50%). Students' self-confidence levels were also high, with indicators of courage to express opinions (87.50%), active participation in learning (71.88%), and confidence in their abilities (90.62%). Therefore, Pancasila Education teachers play a crucial role in fostering student self-confidence through active and participatory learning.